THE ROLE AND IMPORTANCE OF THE FAMILY INSTITUTION IN SOCIAL STABILITY (Universal International Scientific Journal, 2026)
This article analyzes the institution of the family as the main social support ensuring the stability of society from a socio-philosophical point of view. The role of the family in the upbringing of the individual, the formation of moral values, the coherence of social relations and the development of civic responsibility is highlighted. The inextricable link between the stability of the family and the development of society is also revealed, and the theoretical importance of strengthening the family in the conditions of modern social processes is substantiated.
Keywords: family institution; family upbringing; social capital